A Contrastive Analysis of Adjective Structure in Indonesian and Arabic and the Implication in Teaching Arabic | Tahlīl At-Tarkīb An-Na - Amami Shofiya Al Qorin; Afifah Akmalia; A. Syaifudin; Diandra Ariesta Lily Effendy; Imam Asrori (Universitas Islam Negeri Palangka Raya, 2022)
Indonesian as a mother tongue has characteristics that distinguish it from Arabic. The existing differences cause difficulties in learning Arabic. This study aims to conduct a contrastive analysis of adjective phrases between Indonesian and Arabic and explain the implications of the results in learning Arabic. This study is library research on Arabic and Indonesian literature by collecting data in adjective phrase examples using listening and note-taking method. The results of this study show similarities and differences between Indonesian and Arabic adjective phrases. The existing similarities include: 1) similarities in the order of forming elements of the adjective phrase, 2) similarities in the purpose of the phrase-forming elements, 3) similarities in the position of the phrase, specifically in mubtada', khabar, subject, object, and syibhu al-jumlah. Meanwhile, the differences between adjective phrases lie on the compatibility between the phrase-forming elements that exist in Arabic adjective phrases but are not applicable in Indonesian, which are muannats-mudzakkar, ma'rifah-nakirah, number and position of the phrase in a sentence. The results of this contrastive analysis in learning Arabic have direct implications for predicting students' errors when studying Arabic adjective phrase, sorting teaching materials and selecting learning strategies for Arabic adjective phrase.